Digital innovation in Jingdezhen ceramic sculpture: balancing tradition and modernity - Jiaqi, Fu; Abu Hassan, Sharmiza; Mohammad Noh, Liza Marziana; Na, Ma (Faculty of Art and Design, 2025)
This research examines the intricate interplay between traditional craftsmanship and digital innovation in the contemporary practice of Jingdezhen ceramic sculpture. As a globally significant center for ceramic art with a profound history, Jingdezhen is at a critical juncture where its cultural heritage confronts the transformative potential of digital technologies. This transformation lies in a core conflict between the preservation of intangible cultural heritage and the drive for technological advancement. Employing a qualitative methodology grounded in in-depth interviews with master artisans and ethnographic case studies, this research examines how digital tools, such as 3D printing and computer-aided design, are being integrated into creative processes. The findings reveal that the primary barriers to integration are not technical but are deeply rooted in cultural and ideological frameworks. This situation reflects a significant dilemma in value perception, whereby labor-intensive, process-oriented practices such as mold making are often margnialised in favor of decorative artistry, thus fostering resistance to the adoption of technological innovations. The research argues that successful integration hinges on more than mere technological adoption; it requires a fundamental recalibration of existing value systems. It proposes a framework for a symbiotic innovation strategic approach that reaffirms the cultural and artistic value of traditional craftsmanship while leveraging digital technologies to enhance precision, explore novel forms, and augment artistic expression. This study contributes a critical analysis of the challenges and opportunities facing a heritage craft in the digital age, offering implications for cultural policy, arts pedagogy, and the sustainable future of traditional craftsmanship worldwide.